Prognostic Value of N-terminal B-type Natriuretic Peptide in Patients with Acute Myocardial Infarction: A Multicenter Study - Koh, K.T.; Tan, S.S.N.; Sim, P.P.; Tiong, L.L.; Ku, M.Y.; Hoo, W.S.Y.; Wong, L.T.; Yong, K.Y.; Lau, K.T.; Chandan, D.B.; Fong, S.I.; Sia, T.L.L.; et al. (Elsevier, 2017)
Background: Several models have been developed to help the clinician in risk stratification for Acute Coronary Syndrome (ACS),such as the TIMI and GRACE risk scores. However, there is conflicting evidence for the prognostic value of NT-ProBNP in acute myocardial infarction (AMI). Objective: (1) To explore the association of NT-proBNP with 30-day clinical outcome in AMI patients. (2) To compare the prognostic value of NT-proBNP with TIMI and GRACE risk scores in AMI patients. Methods: We conducted a multicenter, prospective observational study recruiting patients presented with AMI between 29-October-2015 and 14-January-2017, involving 1 cardiology referral centre and 4 non-cardiology hospitals. NT-proBNP level (Alere Triage®, US)was measured within 24 hours fromthe diagnosis of AMI. Patientswere followed-up for 1 month. Results: A total of 186 patients were recruited, 143 from tertiary cardiology centre and 43 from non-cardiology hospitals. Mean age was 54.7±10.0 years, 87.6% male and 64% were STEMI. The NT-proBNP level ranged from 60 to 16700pg/ml, with a median of 714pg/ml. Using the 75th centile as the cutoff, Kaplan-Meier survival analysis for the 30-day cardiac related mortality was significantly higher for patient with NT-proBNP level of ≥1600pg/ml (6.4% vs. 0.7%, p=0.02). Cox-regression analysis showed that NT-proBNP level of ≥1600pg/ml was an independent predictor of 30-day cardiac related mortality, regardless of TIMI risk score, GRACE score, LV ejection fraction and study hospitals (HR 9.274, p=0.054, 95%CI 0.965, 89.161). Readmission for heart failure at 30-day was also higher for patient with NT-proBNP level of ≥1600pg/ml (HR 9.308, p=0.053, 95%CI 0.969, 89.492). NT-proBNP level was not associated with all-cause mortality, risk of readmission for ACS, arrhythmia and stroke (pN0.05). By adding 50 score to GRACE risk score for NT-proBNP level of ≥1600pg/ml, combination of GraceNT-proBNP scores of more than 200 appeared to be a better independent predictor for 30-day cardiac related mortality (HR:28.28, p=0.004, 95%CI 2.94, 272.1). ROC analysis showed that this new score had 75% sensitivity and 91.2% specificity in predicting 30-day cardiac related mortality (AUC 0.791, p=0.046). Conclusions: NT-proBNP is a useful point-of-care risk stratification biomarker in AMI. It can be combined to the current risk score model for better risk stratification in AMI patients.